Mechanisms and functions of the cerebral-cognitive reserve in patients with Alzheimer's disease: a narrative review - Alena P. Sidenkova; Vasilisa V. Litvinenko; Vladimir V. Bazarny; Alexei V. Rezaikin; Alexander V. Zakharov; Lyudmila T. Baranskaya; Ekaterina Ivanovna Babushkina (Consortium Psychiatricum)
BACKGROUND: The need for scientific knowledge about aging is predicated on the demand of modern society to extend the active life of a person. To maintain intellectual longevity, it is necessary to take into account not only the pathological, but also compensatory mechanisms that arise during aging. The cerebral-cognitive reserve (CCR) influences the rate of transition from pre-phenomenological stages to the clinical stage of the disease, thereby changing the prognosis of Alzheimer’s disease (AD).